2021
DOI: 10.4103/jod.jod_28_18
|View full text |Cite
|
Sign up to set email alerts
|

Admission Hyperglycemia and its Implications on Outcome in Patients Attending Medical Intensive Care Units at Assiut University Hospital

Abstract: Background: Admission hyperglycemia is defined as any blood glucose (BG) level greater than 140 mg/dL (>7.8 mmol/L) in critical care unit (CCU) according to American Diabetes Association 2015. Stress hyperglycemia is related to multiple factors and can lead to insulin resistance and high hepatic glucose output. Aim: To determine the frequency, in-hospital mortality, and length of stay in a cohort of patients with admission hyperglycemia in unselected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…23 It makes researchers turn to the relationship between the degree of premorbid glycaemia and mortality, the admission blood glucose levels are especially proved associated with higher mortality. 24 Researchers had concluded that admission hyperglycemia could result from a combination of acute physiological stress or higher baseline blood glucose. 25 Quantification of the level of chronic glycemia in critically ill patients provides important clinical information how severity critical illness-associated dysglycemia is.…”
Section: Discussionmentioning
confidence: 99%
“…23 It makes researchers turn to the relationship between the degree of premorbid glycaemia and mortality, the admission blood glucose levels are especially proved associated with higher mortality. 24 Researchers had concluded that admission hyperglycemia could result from a combination of acute physiological stress or higher baseline blood glucose. 25 Quantification of the level of chronic glycemia in critically ill patients provides important clinical information how severity critical illness-associated dysglycemia is.…”
Section: Discussionmentioning
confidence: 99%
“…Fawzy 29 reported that the elevated glycemic gap between the admission blood glucose and the previous glycemic level was associated with an increased ICU mortality, and the predictive power for the mortality of critically ill patients was improved effectively with the APACHE II score incorporated 30 . Meanwhile, the stress hyperglycemia ratio, that is, the fasting glucose concentration at admission divided by the ADAG, confirmed by Fabbri et al 31,32 , was predictive of mortality following admission for sepsis, and it may be used to refine the prediction of an unfavorable outcome.…”
Section: Discussionmentioning
confidence: 99%